Dietary supplementation with honeycomb extracts positively improved egg nutritional and flavor quality, serum antioxidant and immune functions of laying ducks - Chen, Xiaolian; Xiong, Pingwen; Song, Wenjing; Song, Qiongli; Zou, Zhiheng; Huang, Jiangnan; Chen, Jiang; Xu, Chuanhui; Su, Weide; Ai, Gaoxiang; Wei, Qipeng (Frontiers in Veterinary Science, 2023)
Introduction Honeycomb is a traditional natural health medicine and has antioxidant, antibacterial, anti-inflammatory, antiviral and antitumor activities. It is currently unclear whether honeycomb extract supplementation has positive effects on the intensive farming laying duck production. This study aims to evaluate the effects of honeycomb extracts on the laying performance, egg nutritional and flavor quality, serum biochemical indexes, and antioxidant and immune status in laying ducks. Methods A total of 672 healthy 28-week-old Shanma laying ducks with similar laying performance and body weight were randomly distributed into four dietary treatments with 6 replicates of 28 birds. The birds in each treatment were fed the basal diet supplemented with 0 (control group), 0.5, 1.0 or 1.5 g/kg honeycomb extracts, respectively. Feed and water were provided ad libitum for 45 days. Laying performance, egg quality, egg nutrition and flavor quality, serum parameters were assessed. Results The results showed that compared with the control group, honeycomb extracts addition significantly increased the average daily feed intake but did not affect the other laying performance indexes, egg quality or serum biochemical indexes of laying ducks. Dietary supplementation with honeycomb extracts significantly increased crude protein content and decreased the contents of cholesterol and trimethylamine in eggs. Diets supplemented with 1.5 g/kg honeycomb extracts significantly improved egg total amino acids and flavor amino acids contents, monounsaturated fatty acids and polyunsaturated fatty acids composition and enhanced the serum antioxidant activity and immune functions of ducks. Discussion Duck eggs are rich in nutrients and a valuable source of high-quality food for human, while they are rarely consumed directly by consumers because of their stronger fishy odor and lower sensory quality. Many studies have showed that the influence of dietary supplementation on egg components. This study indicated that dietary supplementation with honeycomb extracts positively reduced the contents of egg cholesterol and trimethylamine, improve egg amino acids contents and fatty acid profiles, enhanced serum antioxidant and immune status of laying ducks. The recommended supplemental level of honeycomb extracts was 1.5 g/kg in the diet of laying ducks.